Microbial community profiling of peripheral blood in myalgic encephalomyelitis/chronic fatigue syndrome. (August 2018) - Ellis, Jeremy E.; Missan, Dara S.; Shabilla, Matthew; Martinez, Delyn; Fry, Stephen E.
Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is estimated to afflict hundreds of thousands, if not millions, of Americans with vastly more impacted individuals worldwide; however, the etiology of this disease has not been well established. Based on the features of ME/CFS, we hypothesized an unrecognized vascular infection may be involved. To evaluate this possibility, we performed a blinded pilot study of 30 ME/CFS patients meeting the Fukuda criteria and 48 normal controls. A community-wide analysis using next-generation DNA sequencing methods detected prokaryotic and eukaryotic populations in the peripheral blood of both ME/CFS patients and normal controls. Analysis of the prokaryotic portion of the samples revealed that organisms belonging to the Pseudomonas asplenii species, Pseudomonadaceae family, Pseudomonadales order, and γ-proteobacteria class are inversely correlated with RAND-36 scores, a quality of life metric that is reduced in ME/CFS patients. In addition, analysis of the detected eukaryotic species suggests that the Perkinsus genus is also inversely associated with RAND-36 scores. The most frequently observed eukaryotic DNA was for Funneliformis mosseae, an arbuscular mycorrhizal fungus, which was in both ME/CFS and normal control samples. A multivariate composite score consisting of the Perkinsus genus, Spumella genus, and β-proteobacteria class displays an inverse relationship to RAND-36 scores. Lastly, the combined measurements of several taxa allow for a retrospective categorical sorting of ME/CFS patients from normal control samples. These results suggest that microbial DNA signatures, including those from poorly understood eukaryotes, may be differentially detectable in ME/CFS and normal control samples.